Increasing 2-methyl-1-butanol tolerance of prokaryotic industrial strains by using randomized libraries of camp receptor protein. - Khoo, Choon Mong. (2010)
2-methyl-1-butanol is a promising biofuel which could replace the world’s dependence on petroleum diesel. However, industrial production of this alcohol using biocatalyst is inefficient. The average cost of producing a unit of 2-methyl-1-butanol is more than that of petroleum diesel. Hence, better biocatalyst has to be engineered for better rate of production. To discover prokaryotic industrial strains with high tolerance for 2-methyl-1-butanol, CRP which is a well-investigated global transcription factor in Escherichia coli is mutated. Error-prone PCR was administered on the crp gene which was then inserted into a pKSC101 plasmid. This recombinant plasmid was transformed into competent E. coli DH5 alpha cells. Subsequently, the transformed cells were investigated for the desired phenotype. This investigation was done based on the directed evolution concept. Three better strains were discovered with their mutations determined. E. coli with shortened crp gene were found to be more resilient towards 2-methyl-1-butanol. However, there was no evidence suggesting how shortened crp gene was going to affect genetically engineered prokaryotic industrial strains production of the 2-methyl-1-butanol.